Memahami Makna Ijazul Ilmi dalam Fenomena Air Laut yang Terdapat dalam Surah Arrahman Ayat 19 - Abdul Bukhori Hafis; Hanafi Nasution Mahathir; Muhammad Hutasuhut (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
The discourse regarding al-i'jaz al-'ilmi is a contemporary issue in the i'jaz al-Qur'an, especially if it is related to the discourse on the integration of science and religion. This is in line with the view that the Qur'an contains al-i'jaz al-'ilmi, so that it provides motivation and guidance for the development of science. However, errors in integrating science and religion will give birth to "pseudoscience" or "pseudoscience" which of course is not scientific. Even more than that, someone will be trapped in the "religiousization" of science or "sainization" of religion which assumes that religion and science can complement, complement and correct each other. Therefore, within the framework of the Philosophy of Science with library research type research, this article presents a study of the possibility of developing science based on the Koran. Even though there have been efforts to root scientific findings in the Koran, from the perspective of the Philosophy of Science, this is not necessarily science based on the Koran, in fact it may not even be science, but simply a layman's choice which is non-scientific. There is a pattern of scientific development which, although based on religion, still has scientific value, consisting of three layers of philosophical basis, namely theoretical framework, scientific paradigm and theological basis. By carefully following this pattern, the development of science can not only avoid pseudoscience, but will also give birth to science with high scientific value within the framework of the Koran. Then the development project is carried out with institutional-collective-cultural work.